Patient-reported Goal Achievement after Treating Male Benign Prostatic Hyperplasia with Alpha-adrenergic Antagonist: A 12-week Prospective Multicenter Study - Kim, Bum Soo; Kim, Tae-Hwan; Kim, Ki Ho; Kim, Byung Hoon; Ha, Ji Yong; Cho, Deok Hyun; Kim, Gun Nam; Lee, Yoon Hyung; Kim, Jae Soo; Jung, Hyun-Jin; Shin, Hong Seok; Song, Phil Hyun; et al. (Urology Journal, 2019)
Purpose: The study was designed to assess and predict patient-reported goal achievement after treatment of benign prostatic hyperplasia (BPH) patients with tamsulosin. Materials and methods: From November 2013 to October 2015, 272 patients initially diagnosed with BPH were prospectively enrolled in nine different centers. Before the treatment, subjective final goals were recorded by all patients. Every four weeks, the treatment outcomes were evaluated using international prostate symptom score (IPSS) and uroflowmetry, and adverse events were recorded. Patient-reported goal achievements were assessed after 12 weeks of treatment. Results: Of the enrolled patients, 179 patients completed the study. The pretreatment patients’ goals included the frequency improvement, nocturia improvement, residual urine sense improvement, well voiding, hesitancy improvement, weak urine stream improvement, urgency improvement, and voiding-related discomfort improvement. Of the 179 patients, 129 patients (72.1%) reported that they achieved their primary goals after three months of medical therapy. Logistic regression analysis revealed that pretreatment quality of life (OR = 8.621, 95% CI: 2.154-9.834), and improvement of quality of life (OR = 6.740, 95% CI: 1.908-11.490) were independent predictors of patient-reported goal achievement after tamsulosin monotherapy. Conclusion: Overall patient-reported goal achievement after medical therapy for BPH was high and the scores of pretreatment quality of life and improvement of quality of life can be important factors to predict the achievement of treatment goals.